Effectiveness of Lumbar Transforaminal Epidural Steroid Injection in Patients with Radiculopathy - A Prospective Observational Study - Agrawal, Dr Aveek; I, Dr Praveen; VV , Dr Subramanian; Moorthy A, Dr Vinayaga (South Eastern European Journal of Public Health, 2024)
Background: Lumbar radiculopathy is a common condition characterized by pain radiating from the lower back to the lower limb, with high prevalence rates in the Indian population. Objectives: To evaluate the effectiveness of lumbar transforaminal epidural steroid injections in patients with radiculopathy. Materials and Method: The present study included 31 patients with intervertebral disc prolapse and radiculopathy confirmed by MRI. Patients received lumbar transforaminal epidural steroid injection and were assessed at baseline, immediately after, and at 6, 12, and 24 weeks using Numerical Rating Scale (NRS), Oswestry Disability Index (ODI), and Patient Satisfaction Questionnaire-18 (PSQ-18). A statistically analysis was carried using the Friedman test and Post-hoc Wilcoxon signed rank test with p<0.005 as significant value. Results: Numerical Rating Scale (NRS) scores decreased substantially from 6.81 to 3.45 immediately after the procedure and remained low at 6-12 weeks (3.42-3.74), with a slight increase at 24 weeks (4.23). Similarly, Oswestry Disability Index (ODI) scores improved notably from 44.19 to 29.16 immediately after the procedure and remained improved at 6-24 weeks (30.00-33.48). Patient Satisfaction Questionnaire-18 (PSQ-18), showed a brief improvement post-procedure (4.09) but returned to near baseline levels (3.97-4.01) over the long-term follow-up period. These findings were statistically significant, with p-values of 0.000 for NRS, ODI, and PSQ-18 scores over follow-ups. Conclusion: Transforaminal epidural steroid injection is a safe and effective treatment for lumbar radiculopathy, providing short-term pain relief and functional improvement. However, long-term efficacy remains unclear, highlighting the need for further large-scale, long-term research to optimize treatment outcomes.